ANALYSIS OF MASAMO CATFISH MARKETING BY ANALYTICAL APPROACH AT FARMER GROUP “SUMBER LANCAR”, BLIMBING, MALANG CITY - Abidin, Zainal; Handayani, Wahyu; Fattah, Mochammad (Faculty of Fisheries and Marine Science, Brawijaya University, 2016)
Masamo as new variety of catfish cultivated by the farmer group